PECULIARITIES OF STRUCTURE FORMATION OF THE CONSTRUCTIONAL ALLOYED STEEL AT HEAT TREAT MENT OF HIGHQUALITY ROLLED IRON - V. A. Lutsenko; P. A. Bobkov; T. N. Golubenko; L. A. Drobyshevsky; V. I. Gritsayenko (Литьë и металлургия)
The structure formation in electric steel 42Cr4Mo2 under continuous cooling is investigated, the results are summarized in the form of the thermo-kinetic diagram. It is shown that rolled metal annealing during 3.5-4.0 hours at 650-680°C provides the necessary properties of steel and enables to maintain energy consumption.